Fair Value measurements in the Big Data environment and the effects of the health crisis COVID-19 - Ykhlef , Imane (Journal of Research in Finance and Accounting, 2022)
This paper aims to discuss the impact of Big Data on the Fair Value Measurements during the COVID-19 Pandemic, we relied on the inductive method using the description tool, this is by presenting the conceptual framework for both big data and fair value measurement based on previous research and studies, and then we deduced the impacts among them and linking the findings from this emerging relationship to the repercussions of the current health crisis, all of this, is based on the analytical method. We conclude that Fair Value measurement has become difficult because of uncertain estimates due to the current economic conditions in light of the repercussions of the Corona virus, this leads to thinking about finding the best alternatives for measuring the Fair Value in the current circumstances, which will reduce personal judgments and assumptions. Big data, can exceed the ability of traditional technologies in dealing with the current economic conditions, which are dominated by a state of uncertainty and certainty, where it will work to raise the quality of information and data that the market needs, and this is an advanced manner and somewhat free from assumptions, and responding to various requirements in Real Time.